Microorganisms and composted sewage sludge in the initial development of baru seedlings in pots - Silva, Philippe Solano Toledo [UNESP]; Prates, Adrielle Rodrigues [UNESP]; Fernandes, Dirceu Maximino [UNESP]; Cassiolato, Ana Maria Rodrigues [UNESP]; Maltoni, Katia Luciene [UNESP] (FapUNIFESP (SciELO), 2022)
The Brazilian Cerrado has a great diversity of plants and acidic soils with reduced availability of some nutrients, such as phosphorus (P). Addition of organic residues and microorganisms could help to establish plants in this environment. The aim of this work was to evaluate the initial development of baru (Dipteryx alata) seedlings, through the availability of nutrients (such as P) by fertilization with composted sewage sludge (SLUDGE) with sugarcane bagasse (1:1) and inoculated with Bacillus subtilis and arbuscular mycorrhizal fungus (AMF) Glomus clarum. The experiments were carried out in a greenhouse, with an experimental design in randomized blocks, in a 2 × 4 factorial scheme, being: SLUDGE (with and without) and inoculation (1 = Control; 2 = B. subtilis, 3 = Gl. clarum and 4 = B. subtilis + Gl. clarum), with 5 replications and one seedling per pot. After 150 days of transplanting the seedlings, the following parameters were evaluated: fresh and dry biomass of the aerial part; stem diameter; plant height; number of leaves; seedling quality index; fresh and dry biomass, surface area, volume, total length and mean diameter of roots; root colonization (COL) and number of AMF spores; COL by melanized septate endophytes (DSE) and carbon from CO2 (C-CO2) released. The baruzeiro showed to be an undemanding species in terms of fertilization, but responsive to inoculation, showing increments in fresh biomass, surface area, volume and total length of roots. The inoculation with Gl. clarum increased the number of spores and the rate of C-CO2 released into the soil, while Gl. clarum and B. subtilis increased COL by AMF and DSE.
Microrganismos e lodo de esgoto compostado no desenvolvimento inicial de mudas de baru em vasos
Keywords: cerrado; composted sewage slugde; Dipteryx alata Vogel; growth promoters